Improving Science Learning Outcomes for Class VII.B SMP Negeri 47 South Konawe Through the “Switch Partner” Technique - ernawati ernawati (Persatuan Guru Republik Indonesia Provinsi sulawesi Tenggara, 2021)
This study aims to improve student learning outcomes in science subjects through cooperative learning with the